The African Court of Justice and human and peoples' rights in context : development and challenges - Jalloh, Charles C.; Clarke, Kamari Maxine, 1966-; Nmehielle, Vincent Obisienunwo Orlu (Cambridge : Cambridge University Press, 2019)
The treaty creating the African Court of Justice and Human and Peoples' Rights, if and when it comes into force, contains innovative elements that have potentially significant implications for current substantive and procedural approaches to regional and international dispute settlements. Bringing together leading authorities in international criminal law, human rights and transitional justice, this volume provides the first comprehensive analysis of the'Malabo Protocol' while situating it within the wider fields of international law and international relations. The book, edited by Professors Jalloh, Clarke and Nmehielle, offers scholarly, empirical, critically engaged and practical analyses of some of its most challenging provisions. Breaking new ground on the African Court, but also treating old concepts in a novel and relevant way, The African Court of Justice and Human and Peoples' Rights in Context is for anyone interested in international law, including international criminal law and international human rights law. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 09 May 2019).
Keywords: International human rights courts -- Africa; International criminal courts -- Africa; Criminal justice, Administration of -- Africa; International criminal law -- Africa